Пределы рациональных и иррациональных функций: программированное учебное пособие / В. В. Куликов - Куликов Владимир Владимирович (1972)
Экземпляры: КХ (20210329) / Инвентарный номер: 0212615 / Сис.шифр: 517.2 / Авт.знак: К 90 / ГРНТИ: 27 / ББК: 22